Study of bio-oil and bio-char production from algae by slow pyrolysis - K. Chaiwong (2018)
This study examined bio-oil and bio-char fuel produced from Spirulina Sp. by slow pyrolysis. A thermogravimetric analyser (TGA) was used to investigate the pyrolytic characteristics and essential components of algae. It was found that the temperature for the maximum degradation, 322°C, is lower than that of other biomass. With our fixed-bed reactor, 125g of dried Spirulina Sp. algae was fed under a nitrogen atmosphere until the temperature reached a set temperature between 450 and 600°C. It was found that the suitable temperature to obtain bio-char and bio-oil were at approximately 500 and 550°C respectively. The bio-oil components were identified by a gas chromatography/mass spectrometry (GC-MS). The saturated functional carbon of the bio-oil was in a range of heavy naphtha, kerosene and diesel oil. The energy consumption ratio (ECR) of bio-oil and bio-char was calculated, and the net energy output was positive. The ECR had an average value of 0.49. © 2013 Elsevier Ltd.